RETRACTED: The Impact of Corporate Social Responsibility on Sustainable Innovation: A Case in China’s Heavy Pollution Industry - Yan, Rui; Li, Xiaolin; Zhu, Xiaoning (Frontiers in Psychology, 2022)
In the context of increasingly prominent pollution problems, exploring the impact of corporate social responsibility fulfillment and disclosure on enterprises’ sustainable innovation capacity can not only expand the research boundary of factors sustainable innovation and the impact of corporate social responsibility, but also provide reference for the decision-making of listed companies. Using a sample from 224 companies of heavy pollution industry A-share listed in China between 2016 and 2020 and adopting an ordinary least square regression, firstly, the results provide empirical evidence showing that corporate social responsibility is positively associated with sustainable innovation. Second, business environment can be a moderating variable of the relationship between corporate social responsibility and sustainable innovation, and the promoting effect between corporate social responsibility and sustainable innovation is more obvious when enterprises are located in regions with better macroeconomic conditions. Additionally, compared with non-state-owned enterprises, the improvement of corporate social responsibility on sustainable innovation is more obvious in state-owned enterprises. The results are still hold after a series of robustness tests and eliminate the interference of the marketization, the law enforcement and macro political uncertainty. This study expands the research boundary of corporate social responsibility and sustainable innovation. Furthermore, this study conclusions of this paper are of reference significance both in theory and practice.